Silver Nanoparticles Synthesized with Extracts of Leaves of Raphanus sativus L, Beta vulgaris L, and Ocimum basilicum and Its Application in Seed Disinfection - Cristina Garcidueñas-Piña; Carolina Tirado-Fuentes; Julio Ruiz-Pérez; Roberto Carlos Valerio-García; José Francisco Morales-Domínguez (Nanomaterials and Nanotechnology)
Silver nanoparticles (AgNPs) were produced by green synthesis using Raphanus sativus (RsAgNPs), Beta vulgaris (BvAgNPs), and Ocimum basilicum (ObAgNPs) leaf extracts as reducing agents. Plant phytochemical composition analysis indicated that they contain phenolic compounds that can participate in the synthesis reaction as flavonoids. Synthesized AgNPs presented maximal absorption peak at 430 nm (RsAgNP), 440 nm (BvAgNP), and 420 nm (ObAgNP) in ultraviolet-visible spectrophotometry analysis. Scanning electron microscopy and energy dispersive X-ray spectroscopy analysis showed that RsAgNPs are 76 nm diameter spheres made of up to 54.1% silver, the BvAgNPs are 78 nm diameter spheres with 39.76% silver, and the ObAgNPs are cubes of 99 nm edges with 69.74% silver. The found Z potential values indicate that all the obtained AgNPs are stable in phosphate buffer. A disinfection of 100% and 90% was achieved for the in vitro culture of Arabidopsis thaliana and Psidium guajava (guava) seeds, respectively, with all AgNPs synthesized. Treatment with these AgNPs showed no negative effects on germination, and on the contrary, in guava, a higher germination percentage was observed when the seeds were exposed to RsAgNPs. Only at high concentration (10 mg/mL) of AgNPs, the growth of A. thaliana was decreased, while at low concentration (0.01 mg/mL) of ObAgNP and BvAgNPs, higher growth was showed, specifically 60 and 40% more than the control, respectively. All AgNPs showed antimicrobial activity against Escherichia coli and Klebsiella oxytoca which are bacteria of clinical interest, and against Agrobacterium tumefaciens, a bacterium used in the genetic transformation of plants.